2019
DOI: 10.3390/polym11010127
|View full text |Cite
|
Sign up to set email alerts
|

Description of the Resin Curing Process—Formulation and Optimization

Abstract: The paper gives a set of basic relations characterizing the phenomena of viscous polymer resin flow through fiber reinforcement and the resin curing process. We describe the technological process of manufacturing composite structures. The influence of the resin curing process on values of residual stresses in composite constructions is analyzed taking into account two components: thermal shrinkage and chemical shrinkage of resins. For cases of 2-D structures, the method of formulating such tasks has been demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 82 publications
(145 reference statements)
0
14
0
Order By: Relevance
“…In defected areas lowering of density and thermal conductivity is observed, and also the thermal diffusivity is different, what finally influences on heat transfer within the material. 13,19,20 Diffusivity a (m 2 s À1 ) is given by…”
Section: Theoretical Formulationmentioning
confidence: 99%
“…In defected areas lowering of density and thermal conductivity is observed, and also the thermal diffusivity is different, what finally influences on heat transfer within the material. 13,19,20 Diffusivity a (m 2 s À1 ) is given by…”
Section: Theoretical Formulationmentioning
confidence: 99%
“…Previously published work on cure-dependent resin behavior mainly focused on better understanding of conventional prepreg and RTM manufacturing processes [1][2][3][4]. Only few attempts were made to analyze the process-dependent properties of fast curing resins [5,6]. Furthermore, pressure dependence is often neglected, which is questionable when it comes to newly developed technologies with high impregnation speed like high pressure RTM (HP-RTM) or wet compression molding [7].…”
Section: Intr Introduction Oductionmentioning
confidence: 99%
“…Guan [ 25 ] optimised the curing cycle for T800/X850 carbon fibre-reinforced plastic while ensuring mechanical properties. Muc [ 26 ] proposed a two-dimensional simulation method to discuss the influence of the resin curing process on residual stresses in thick thermosetting composites and concluded that by choosing an optimised curing cycle, the residual stresses could be reduced substantially. Lee [ 27 ] measured the temperature distribution in a 20 mm-thick unidirectional glass/EP laminate in the autoclave process and compared it with numerical results.…”
Section: Introductionmentioning
confidence: 99%